Role of Community and User Attributes in Collective Action: Case Study of Community-Based Forest Management in Nepal - Negi, S.; Pham Thu Thuy; Karky, B.; García, C. (MDPI, 2018)
A growing literature on collective action focuses on exploring the conditions that might help or hinder groups to work collectively. In this paper, we focus on community-based forest management in the inner Terai region of Nepal and explore the role of community and user attributes such as group size, social heterogeneities, forest user’ perception on forests, and affiliation to the user group, in the collective action of managing community forests. Household surveys were carried out with 180 households across twelve community forest users’ groups. We first measured ethnic diversity, income inequality, landholding inequality, and user perception towards the use and management of community forests to understand their effect on the participation of forest users in the management of community forests. Our results show that among the studied variables, group size (number of forest users affiliated to the community forests) and perception of the management of their community forests are strong predictors of forest user participation in community forest management. Income inequality and ethnic diversity were found to have no significant association. Land inequality, however, was found to decrease participation in the management and use of community forests. These community and user attributes play a crucial role in the success of collective action and may vary from community to community. Hence they need to be duly considered by the practitioners prior to any community-based project interventions for stimulating successful collective action.